Transcriptome Analysis and Genome-Wide Gene Family Identification Enhance Insights into Bacterial Wilt Resistance in Tobacco - Liu, Zhengwen; Xiao, Zhiliang; Geng, Ruimei; Ren, Min; Wu, Xiuming; Xie, He; Bai, Ge; Zhang, Huifen; Liu, Dan; Jiang, Caihong; Cheng, Lirui; Yang, Aiguo (Agronomy (Basel), 2024)
Bacterial wilt, caused by the Ralstonia solanacearum species complex, is one of the most damaging bacterial diseases in tobacco and other Solanaceae crops. In this study, we conducted an analysis and comparison of transcriptome landscape changes in seedling roots of three tobacco BC4F5 lines, C244, C010, and C035, with different resistance to bacterial wilt at 3, 9, 24, and 48 h after R. solanacearum infection. A number of biological processes were highlighted for their differential enrichment between C244, C010, and C035, especially those associated with cell wall development, protein quality control, and stress response. Hence, we performed a genome-wide identification of seven cell wall development-related gene families and six heat shock protein (Hsp) families and proposed that genes induced by R. solanacearum and showing distinct expression patterns in C244, C010, and C035 could serve as a potential gene resource for enhancing bacterial wilt resistance. Additionally, a comparative transcriptome analysis of R. solanacearum-inoculated root samples from C244 and C035, as well as C010 and C035, resulted in the identification of a further 33 candidate genes, of which Nitab4.5_0007488g0040, a member of the pathogenesis-related protein 1 (PR-1) family, was found to positively regulate bacterial wilt resistance, supported by real-time quantitative PCR (qRT-PCR) and virus-induced gene silencing (VIGS) assays. Our results contribute to a better understanding of molecular mechanisms underlying bacterial wilt resistance and provide novel alternative genes for resistance improvement.